Cuffed-tunneled catheters in hemodialysis patients: problems and solution methods: A single-center retrospective cohort study: Cuffed-tunneled catheters - Yardımcı, Mümtaz Murat; Güven , Cengiz (Journal of Surgery and Medicine, 2023)
Background/Aim: Cuffed-tunneled catheter patients encounter various problems during their catheterization period. Early detection and resolution of these problems prolong the life of the catheter. The purpose of the present study was to investigate the problems and solution methods of cuffed-tunneled catheters in hemodialysis patients during their use in light of our experience and literature. Methods: The study was designed as a retrospective cohort study. Twenty-four months of patient data who had a diagnosis of renal failure and who received cuffed-tunneled hemodialysis catheters between January 2013 and June 21 in the Department of Cardiovascular Surgery of Adiyaman University Faculty of Medicine were analyzed electronically based on the hospital data recording system. The demographic characteristics, localization of the inserted catheter, and duration of catheter use were determined. Primary and secondary patency ratios were calculated and recorded along with the complications in the patients and our treatment approaches to these complications. Finally, the collected data were discussed with reference to the literature data. Results: The data from 322 cuffed-tunneled catheters were collected in a total of 228 patients during the observation period. It was found that no revision procedure was applied to 73 patients (catheter) during the 24-month period, and a total of 204 revision procedures were applied to 155 patients. The revision procedure consisted of 110 thrombolytic treatments, 64 vein exchanges, 18 tunnel changes, and 12 catheter changes. Primary and secondary patency ratios at 6, 12, 18, and 24 months were calculated as 90.79%, 63.60%, 40.11%, and 32.02% and 96.05%, 89.91%, 72.37%, and 58.33%, respectively. The most common factors that affected primary and secondary patency ratios were determined to be gender (P<0.001 and P=0.056, respectively), body mass index (P<0.001 and P<0.001, respectively) and diabetes mellitus (P=0.018 and P=0.690, respectively). Conclusion: Thrombolytic treatment is an effective and safe method in catheter thrombosis, which is one of the most important factors rendering the cuffed-tunneled hemodialysis catheters dysfunctional. Also, in tunnel infections, tunnel replacement is a salvage procedure in patients with vascular access problems.